Crédito e crescimento regional no Brasil: O BNDES versus bancos privados e públicos - Philipp Ehrl; Greisson Almeida Pereira; Vinicius Vizzotto Zanchi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper distinguishes how the source of lending affects gross domestic product (GDP) per capita in Brazilian municipalities between 2007 and 2016. A unique data set allows us to discriminate between the effects of lending operated by either private or public commercial banks, and loans provided by the National Bank for Economic and Social Development (BNDES) either directly or indirectly through accredited financial institutions. Using the system generalized method of moments (System-GMM) estimator, we find that credit from public commercial banks has the highest effect on economic growth because of its regional distribution. Regarding the BNDES, indirect loans were the most robust and significant because this lending facility especially targets firms in small, credit constrained regions, and it was provided non-cyclically.
Keywords: E51; G21; O43; 330; development banks; state-owned banks; regional growth; BNDES